Rasch-Based Cognitive Diagnostic Assessment to Measure Critical Thinking Skills in Islamic Religious Education - Agil Bahsoan; Nurhayati Tine; Ivan Rahmat Santoso; Neva Lionitha Ibrahim; Branislav Pupala (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This research aimed to measure the critical thinking skills of students in the Islamic Religious Education course through the application of a cognitive diagnostic assessment based on the Rasch model. The background of this research stems from the need for an assessment instrument that not only provides summative scores but also diagnoses students’ abilities in a more specific and in-depth manner. It employed a quantitative design involving 107 students, and the developed instrument was validated using Rasch analysis to ensure validity, reliability, and item fit. The results showed that the majority of students are in the moderate category (52,34%), followed by the high category (30,84%), and the low category (16,82%). These results highlight the diversity of students’ critical thinking skills, which require adaptive teaching strategies. The novelty of this research lies not only in the application of the Rasch model in cognitive diagnostic assessment but also in its implementation in the context of Islamic Religious Education, which has traditionally been measured through conventional tests emphasizing memorization and conceptual understanding. This approach allows for a more detailed mapping of critical thinking sub-skills in values- and ethics-based courses, going beyond previous research practices that generally focus on science or technical skills. Thus, this research contributes to the development of more accurate, adaptive, contextual, and relevant assessment instruments to support improvements in the quality of learning in higher education.